2014
DOI: 10.3892/or.2014.3248
|View full text |Cite
|
Sign up to set email alerts
|

Minocycline and cisplatin exert synergistic growth suppression on hepatocellular carcinoma by inducing S phase arrest and apoptosis

Abstract: Minocycline, a semisynthetic tetracycline, is a highly lipophilic molecule capable of infiltrating tissues and blood. Previous studies have revealed the functions and mechanisms of minocycline in anti-inflammation, protection of the nervous system and certain tumors. The role of minocycline has never been investigated in hepatocellular carcinoma (HCC). The functions of minocycline on HCC cells were investigated using immunohistochemical staining and western blotting. Minocycline was applied to L02, HepG2 and H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Adequate data on the appropriate timing of using the minocycline in relation to the cancer treatment course and the short/long-term effects of using minocycline on cancer treatment efficacy/resistance are lacking. Nevertheless, minocycline found to have a synergistic cytotoxicity effect, [31][32][33] and its prophylactic use concurrent with antiepidermal growth factor receptor monoclonal antibodies was not associated with significant influence on tumor response in a retrospective study, 18 thus, safety and efficacy studies before concurrent use of minocycline and cancer treatment are warranted. Although there is a growing role for immunotherapy in the treatment of NSCLC, the safety and efficacy of using minocycline concurrently or shortly after immunotherapy in patients with NSCLC have not yet been investigated.…”
Section: Discussionmentioning
confidence: 95%
“…Adequate data on the appropriate timing of using the minocycline in relation to the cancer treatment course and the short/long-term effects of using minocycline on cancer treatment efficacy/resistance are lacking. Nevertheless, minocycline found to have a synergistic cytotoxicity effect, [31][32][33] and its prophylactic use concurrent with antiepidermal growth factor receptor monoclonal antibodies was not associated with significant influence on tumor response in a retrospective study, 18 thus, safety and efficacy studies before concurrent use of minocycline and cancer treatment are warranted. Although there is a growing role for immunotherapy in the treatment of NSCLC, the safety and efficacy of using minocycline concurrently or shortly after immunotherapy in patients with NSCLC have not yet been investigated.…”
Section: Discussionmentioning
confidence: 95%
“…Moreover, there is evidence that minocycline overcomes resistance to topoisomerase inhibition attenuating the efficacy of irinotecan in peritoneal carcinomatosis [ 38 ]. Additionally, it acts synergistically with cisplatin in the treatment of hepatocellular carcinoma [ 39 ]. In turn, Quinn et al [ 34 ] proved the highly cytotoxic effect of a combination of minocycline with a BH3 mimetic—sabutoclax to pancreatic cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…The study also showed that minocycline decreased the percentage of cells in S and G 2 -M phases, proportionally with concentration. In turn, the profile of changes differs from those observed in hepatocellular carcinoma cells (HCC) [ 39 ]. In this case, minocycline arrested cells in the S phase after 72 h and decreased the percentage of cells in the G 2 -M phase after 24 h and 48 h. At the same time, the number of cells in the G 1 phase did not differ significantly.…”
Section: Discussionmentioning
confidence: 99%
“…The MCM replicative helicase inhibitor (Ciprofloxacin) and the E2F inhibitor (E2Fi), a transcription factor required for regulating expression of S phase genes 32 prevent entry into S phase. Cisplatin (Cis) induces DNA damage by crosslinking DNA, interferes with S-phase progression and arrests cells at G0/G1 phase 33 ; Etoposide (Eto) is a topoisomerase II inhibitor which prevents the unwinding of the DNA helix during replication and transcription and arrests cells mainly in the S and G2 phases 34 ; Aphidicolin (APH) is a DNA polymerase inhibitor which inhibits G1 to S phase transition and S-phase progression in a concentration dependent manner 27 35 . Other tested compounds include pyridostatin (PDS), a compound promoting the formation of G4 structures to induce replication-fork stalling 36 We analyzed the cell cycle progression by labeling cells with EdU for 2 hours on day 26 and collected cells for flow cytometry analysis the next day ( Fig.…”
Section: Inhibition Of S-phase Entry and Compromised S-phase Completimentioning
confidence: 99%